Evaluation of HIV Late Presentation Trends: A Cross-Sectional Analysis from a Leading Ecuadorian Public Hospital - Adriana D. Suarez-Vizcaino; Nicole C. Bustamante-Pancho; Juan S. Izquierdo-Condoy; Hugo Pereira-Olmos; I. Alberto Castillo; Esteban Ortiz-Prado (Pathogens, 2025)
The global impact of HIV is especially significant when diagnoses are made in advanced stages. While strategies exist to mitigate late presentations, Ecuador’s 2018–2022 strategic plan has not yet been evaluated. This study assesses the prevalence and implications of late and advanced HIV presentations in Ecuador, using data from a reference hospital in Quito. A cross-sectional analysis of 436 medical records of people living with HIV from the “Hospital de Especialidades Eugenio Espejo” was conducted between November 2015 and February 2020. The data were divided into “Pre-Plan” and “Post-Plan” periods for comparative analysis. The mean CD4 T count showed a non-statistically significant increase in the post-plan period (January 2018–February 2020). Notably, 65.1% of patients presented late, and 39.4% had advanced disease. Demographic data indicated that 89.9% were men, and 54.1% were under 30 years of age. No characteristics were identified that were associated with advanced late presentation of HIV infection. Sexual orientation data revealed that 69.1% identified as homosexual or bisexual. A predominance of late and advanced presenters was identified in the post-plan period, associated with being employed (p < 0.05) and being drug users (p < 0.001). There was also a greater incidence of late presenters among immigrants in the post-plan period (p = 0.045). Despite the implementation of Ecuador’s 2018–2022 strategic plan for HIV, substantial challenges in reducing late presentations remain. This study suggests that early diagnoses have not significantly improved. Employed patients and drug users were more likely to present late, with drug users also accounting for many advanced cases. This study highlights the need for more focused and targeted strategies to supplement the existing plan.